Impactos ambientais e econômicos dos veículos elétricos e híbridos plug-in: Uma revis\~ao da literatura - Christian Vonbun (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper presents a brief literature review concerning the costs and benefits of electric vehicles and hybrid electric vehicles, highlighting their advantages in terms of greenhouse gas emissions reductions. Even though electric and electro-hybrid vehicles must still overcome many cultural and technological barriers, they present a great potential in improving the energy efficiency of the transportation system, as well as reducing the costs of electric energy production and transmission. The hybrid vehicles may close the technological and operational gap between the old internal combustion powered vehicles and the new electric cars, until new improvements on batteries allow the widespread introduction of electric cars as the standard individual transportation vehicles. Nevertheless, it is imperative to stress that the full potential benefits of these vehicles is conditioned to the implementation of Smart Grids that enable the electric system to use them as a reservoire of energy that provides back up power to the system, to be employed in peak consumption hours. It is also vital to ensure that the required incremental energy production is proportionately cleaner than the internal combustion vehicles they replace.
Keywords: Q43; Q47; Q48; Q50; Q51; Q52; Q53; Q54; Q55; Q56; Q58; 330; electric vehicles; greenhouse effect; emissions; economic evaluation